Clinical and epidemiologic burden of chronic myelogenous leukemia. Issue 1 (1st February 2004) - Redaelli, Alberto; Bell, Christopher; Casagrande, Jodie; Stephens, Jennifer; Botteman, Marc; Laskin, Benjamin; Pashos, Chris
Chronic myelogenous leukemia represents 7––20% of all leukemia cases, with a worldwide incidence projected at less than one to two per 100, 000 people. Approximately 85% of patients are diagnosed with chronic-phase chronic myelogenous leukemia and up to 40% are asymptomatic. Treatment strategies include chemotherapy, interferon-αα therapy, transplantation (bone marrow/stem cell transplant) and imatinib mesylate (Gleevec ®® ), with the impact of treatment best realized during the chronic phase of the disease. Only transplantation has been clinically demonstrated to eradicate the Philadelphia chromosome, alter the natural course of the disease and cure patients diagnosed with chronic myelogenous leukemia. Interferon-αα is currently considered for first-line treatment, however, the recent introduction of targeted therapy may change clinical practice. Ongoing research focused on new drug combinations and target therapies may eventually expand the armamentarium available to cure this disease.